Gulf War and health. (National Academies Press, 2005)
"The third in a series of congressionally mandated reports on Gulf War veterans health, this volume evaluates the long-term, human health effects associated with exposure to selected environmental agents, pollutants, and synthetic chemical compounds believed to have been present during the Gulf War. The committee specifically evaluated the literature on hydrogen sulfide, combustion products, hydrazine and red fuming nitric acid. Both the epidemiologic and toxicologic literature were reviewed."--Publisher's description.